Correlation of acute physiological parameters with immediate outcome among neonates transported to special care newborn unit: A prospective study - Mehta, Nirbhay; Sharma, Manish Kumar (Indian Journal of Child Health, 2018)
Background: Several sick neonates require transfer to tertiary level care neonatal unit for treatment. The facilities of neonatal transport in India are not optimal and the newborn thus transported can become hypothermic, hypoxic, and/or hypoglycemic which can affect the neonatal outcome. These parameters can be maintained during transport by adopting simple measures. Aim: Study impact of acute physiological parameters during transfer of neonates on their immediate outcome by using TOPS score. TOPS Score -temperature, oxygensaturation, perfusion (assessed by capillary refill time), blood Sugar. Materials and Methods: This prospective observational study was conducted at the special care newborn unit, Indore enrolling 513 transported neonates. TOPS scoring for each neonate was done at admission, and then the parameters of the TOPS score were correlated with the outcome at 48 h of admission. Results: A total of 513 transported newborns were assessed, 48.73% newborns were hypothermic, 33.91% had poor perfusion, 28.46% were hypoxemic, and 22.22% were hypoglycemic. Hypoxemia and hypoglycemia had the highest sensitivity (93.39% and 80.18%, respectively) while hypoglycemia had the highest specificity (92.87%). Conclusion: TOPS score is a useful and easy to use the method to assess the physiological status and predict early mortality in transported neonates.